(untitled) (International relations and international law Journal, 2016)
The role of international custom in the legal system of the Republic of Kazakhstan is considered in the article. The author makes reasonable conclusions about the necessity of including the international custom in the legal system of Kazakhstan, which is caused by equality of international treaty and custom and necessity of execution its international legal obligations by the Republic of Kazakhstan